20. EVALUATING OF HEALTH EFFECTS OF CHROMIUM EXPOSURE AMONG CEMENT WORKERS (Vietnam Journal of Community Medicine, 2024)
Exposure to chromium in the workplace can lead to severe health consequences, including skin diseases, respiratory problems.Objective: to assess the current status of chromium exposure and some health effects in cement industry workers.Subject and method: This cross-sectional study, conducted from 2022 to 2023, involved 255 workers exposed to chromium (Cr) in the workplace at three cement plants.Results: The proportion of workers exposed to chromium (VI) > 50 µg/m3 accounted for 20% and urinary chromium ≥ 25 µg/L accounted for 17.3%.The prevalence of skin diseases and restrictive ventilatory disorders among cement workers was 12.2% and 23.1%, respectively. The prevalence of ear, nose, and throat symptoms among workers exposed to chromium dust was relatively high at 35.7%. The median urinary chromium concentration in the dermatological group was 14.12 µg/L. The group of workers with dermatological diseases had a urinary chromium concentration difference of ≥ 25 µg/L that was 3.18 times higher than that of the group without dermatological diseases, with 95% CI of 1.40-7.25%. Not yet relationship was found between urinary chromium and ventilation disorders-ear-nose and restrictive ventilatory disorder diseases.Conclusion: There is a strong association between urinary chromium levels and the risk of developing dermatological diseases.
Keywords: cement; chromium; Occupational diseases